Nutrition in neonatal and pediatric patients on extracorporeal membrane oxygenation: A survey of current practice in the US and Canada - Jamie M. Furlong-Dillard; Michael D. Facciolo; Caroline P. Ozment; and the Pediatric ECMO (PediECMO) Subgroup of the Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) Network and Extracorporeal Life Support Organization (ELSO) (Journal of Pediatric Critical Care)
Background: Patients requiring extracorporeal membrane oxygenation (ECMO) are at increased risk of malnutrition due to high rates of protein catabolism, unclear metabolic needs, and safety risks with both parenteral and enteral nutrition (EN). Malnourishment is associated with increased morbidity and mortality, and improved EN and protein intake are associated with decreased 60-day mortality. A standardized practice for nutrition therapy in this population is unestablished. We aim to provide an update on current nutritional practices in pediatric and neonatal patients receiving ECMO support. Subjects and Methods: An online survey was distributed to ECMO medical directors in the US and Canada who had previously participated in survey-based research and those who requested participation during a pediatric ECMO presentation of this study. Each medical director was asked to forward the survey to their center’s registered dietitians (RDs). Results: Of 100 institutions surveyed, 36 physicians and 19 RDs responded yielding a physician response rate of 36% and an RD response rate of 19%. Physicians report “always” providing nutrition parenterally 28% and enterally 17% of the time with 11% of institutions using a protocolized approach. Nutrition therapy aids reduction of morbidity and mortality; however, there is variability in its delivery. Conclusions: Compared to 2015, EN is reported to be less utilized (47% vs. 55%) with less protocol use (11% vs. 38%). These data support the need for the development of a stepwise nutritional support algorithm, which is congruent with the recommendations in the Extracorporeal Life Support Organization Nutrition Guidelines.